“Contradição entre o nosso ser de religiosas do Bom Pastor e o nosso fazer como funcionárias do governo”: a transição administrativa na Colônia Penal Feminina do Recife (1984-1994). - Lima, Alessandra Silva do Monte (2023)
This report refers to the work carried out in the Professional Master's Degree in History and aims to analyze the transition of administration that occurred in the Colonia Penal Feminina do Recife (CPFR) between the years 1984 and 1994, when the institution ceased to be managed by the nuns of the Congregation of the Good Shepherd, passing into the hands of the State. In the 1940s, the Congregation carried out the task of promoting assistance actions for disadvantaged women in the community and, after an agreement with the Governor of the state, became responsible for the re-education of 20 prisoners. After more than 40 years of activities, the nuns of the Congregation of the Good Shepherd were not satisfied with performing the work of jailers and began to report the difficulties in re-educating the prisoners who were serving time in the prison unit at the time, according to the document entitled “Our Apostolate in Prisons”, resulting from the Meeting of Provincial Superiors of Latin America, held in the city of Bogota, in 1984. In 1990, the nuns left the administration of the institution, starting to be exercised directly by the state power. As support in the theoretical foundation, we use the work “Discipline and Punish”, by Foucault. The research is essentially documentary, analyzing documents and reports from that time, crossing the found information with the papers produced about the Colonia Penal Feminina do Recife, presenting an almanac as a product.